Characterization of the Complete Chloroplast Genome of Acer truncatum Bunge (Sapindales: Aceraceae): A New Woody Oil Tree Species Producing Nervonic Acid. (24th November 2019) - Ma, Qiuyue; Wang, Yanan; Zhu, Lu; Bi, Changwei; Li, Shuxian; Li, Shushun; Wen, Jing; Yan, Kunyuan; Li, Qianzhong
Abstract : Acer truncatum, which is a new woody oil tree species, is an important ornamental and medicinal plant in China. To assess the genetic diversity and relationships of A. truncatum, we analyzed its complete chloroplast (cp) genome sequence. The A. truncatum cp genome comprises 156, 492 bp, with the large single-copy, small single-copy, and inverted repeat (IR) regions consisting of 86, 010, 18, 050, and 26, 216 bp, respectively. The A. truncatum cp genome contains 112 unique functional genes (i.e., 4 rRNA, 30 tRNA, and 78 protein-coding genes) as well as 78 simple sequence repeats, 9 forward repeats, 1 reverse repeat, 5 palindromic repeats, and 7 tandem repeats. We analyzed the expansion/contraction of the IR regions in the cp genomes of six Acer species. A comparison of these cp genomes indicated the noncoding regions were more diverse than the coding regions. A phylogenetic analysis revealed that A. truncatum is closely related to A. miaotaiense . Moreover, a novel ycf4-cemA indel marker was developed for distinguishing several Acer species (i.e., A. buergerianum, A. truncatum, A. henryi, A. negundo, A. ginnala, and A. tonkinense ). The results of the current study provide valuable information for future evolutionary studies and the molecular barcoding of Acer species.